2005
DOI: 10.1111/j.1399-6576.2004.00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal approach to rapid discharge after endoscopic thoracic sympathectomy

Abstract: Multimodal management to rapid discharge after ETS surgery did result in a short time to patient discharge. We confirm that endoscopic thoracic sympathectomy can be performed safely on an outpatient basis with brief postoperative hospital care and a low rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Today, these patients are operated on early in the afternoon programme and discharged the same evening. Due to the underlying pathology of the patients, we think that it would be difficult to improve LB substitution index, but MC-SI could rise to nearly 95%, and most TS could be performed as outpatient procedures as demonstrated by others [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Today, these patients are operated on early in the afternoon programme and discharged the same evening. Due to the underlying pathology of the patients, we think that it would be difficult to improve LB substitution index, but MC-SI could rise to nearly 95%, and most TS could be performed as outpatient procedures as demonstrated by others [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 98%
“…Although the procedure is usually performed in young healthy people, most patients stay one night because of pain, nausea or vomiting. The key to this is anaesthetic technique and premedication with analgesic and antiemetic agents [15,16]. Moreover, systematic intercostal infiltration with local anaesthetic may help in this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendoscopes utilize long, narrow-diameter rod lenses with short focal lengths and “direct in-line” visual trajectories, resulting in a relatively fixed, narrow field of view that is easily obscured with the introduction of surgical instruments or with moderate to brisk bleeding. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…(12)(13)(14)(15) The routine of the procedure varies immensely, taking into account the type of tracheal intubation used, the technique for dissection, blockage or excision of the sympathetic chain, postoperative closed pleural drainage or not, among other aspects. (4,9,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) However, findings in the literature seem to agree on key points: resections of the chain should be as minimal as possible; we should never remove more than one ganglion from the chain; and dissection should begin as caudally as possible, bearing in mind the final objective. (27) In this study, we observed excellent remission rates of palmar and plantar hyperhidrosis, with acceptable rates of compensatory sweating (28) and without any severe or intolerable cases, only by excising completely the third ganglion of the sympathetic chain.…”
Section: Discussionmentioning
confidence: 99%